Unveiling the emergence of functional materials with STM: metal phthalocyanine on surface architectures. Issue 3 (24th May 2019) - Sk, Rejaul; Deshpande, Aparna
Abstract : (a) Self-assembly (SA) of CuPc on the step edges of the Bi2 Se3 surface, b) CuPc 1D chains in the SA, and c) HOMO–LUMO gap variation of CuPc. Abstract : Metal phthalocyanine molecules with their inherent versatility call for an exploration of their fundamental properties when anchored on conducting substrates for designing new applications. In this article we present low temperature scanning tunneling microscopy (LT-STM) and spectroscopy (STS) measurements of copper phthalocyanine (CuPc) on noble metal Au(111), semimetal Bi(111), Dirac material graphene, and topological insulator surface Bi2 Se3 . We discuss in detail how the self-assembly of CuPc varies due to the nature of the substrate. STS measurements enable us to better understand the local electronic properties of the molecule–substrate interface. This insight provides key guidelines for using CuPc towards interface engineering for applications and for unraveling new phenomena therein.